Controversial Role of Robot in Primary and Revisional Bariatric Surgery Procedures: Review of the Literature and Personal Experience - Fantola, Giovanni; Moroni, Enrico; Runfola, Matteo; Lai, Emanuele; Pintus, Stefano; Gallucci, Pierpaolo; Pennestrì, Francesco; Raffaelli, Marco (Frontiers in Surgery, 2022)
Laparoscopy is the surgical standard of care for bariatric procedures, however during the last two decades the robotic approach has gained increasing interest. It is currently considered a safe and effective alternative to laparoscopy. This literature review investigates the role of the robotic approach for primary and revisional bariatric procedures, with the particular aim of comparing this technique to standard-of-care laparoscopic approach. The feasibility of robotic dissection and suturing could have potential advantages: robotic may prevent the risk of leak and bleeding and other surgical complication, determining potential benefits in terms of operative time, length of hospital stay and learning curve. Considering primary procedures, literature reveals no advantages in robotic versus laparoscopic approach for adjustable gastric banding and sleeve gastrectomy. Robotic Roux-en-Y gastric bypass is associated with longer operative time and a shorter hospital length of stay than laparoscopy. Robotic approach in revisional surgery has been proven to be safe and effective. Despite longer operative time, the robotic platform could achieve lower bleeding rate compared to laparoscopy. Surgeon’s selection criteria related to referral to robotic approach of difficult-perceived cases could represent a bias. In conclusion, robotic surgery can be considered a safe and effective approach in both primary and revisional bariatric surgery, despite the lack of evidence to support its routinary use in primary bariatric surgery. However, in revisional bariatric surgery and in surgical complex procedures robotic approach could have potential benefits in terms of surgical complication and learning curve.